A comparative life cycle assessment of dental restorative materials. Issue 1 (January 2023) - Smith, Lucy; Ali, Mustafa; Agrissais, Manon; Mulligan, Steven; Koh, Lenny; Martin, Nicolas
Abstract: Objectives: Different types of direct-placement dental materials are used for the restoration of structure, function and aesthetics of teeth. The aim of this research investigation is to determine, through a comparative cradle-to-gate life cycle assessment, the environmental impacts of three direct-placement dental restorative materials (DRMs) and their associated packaging. Methods: Three direct-placement dental materials; dental amalgam, resin-based composite (RBC) and glass polyalkenoate cements (GIC) are assessed using primary data from a manufacturer (SDI Limited, Australia). The functional unit consisted of 'one dental restoration' of each restorative system under investigation: 1.14 g of dental amalgam; 0.25 g of RBC (plus the adhesive = 0.10 g); and 0.54 g of GIC. The system boundary per restoration included the raw materials and their associated packaging materials for each DRM together with the processing steps for both the materials and packaging. The environmental impacts were assessed using an Egalitarian approach under the ReCiPe method using Umberto software and the Ecoinvent database. Nine different impact categories were used to compare the environmental performance of these materials. Results: Dental amalgam had the highest impact across most of the categories, but RBC had the highest Global Warming Potential. The highest sources of the environmental impacts for each restorative material were: Amalgam, derived from material use; RBC, derived from energy use in processing material and packaging material; GIC, derived from material and energy use for packaging. Significance: Less intensive energy sources or more sustainable packaging materials can potentially reduce the impacts associated with RBC and GIC thus making them suitable alternatives to dental amalgam. Graphical Abstract: ga1 Highlights: The environmental impact of three dental restorative materials was assessed empirically. Nine life-cycle impact assessment categories were investigated with the ReCiPe method. Dental amalgam had the highest and glass ionomers the lowest impact across most categories. Changes in energy mix and packaging materials can potentially reduce the impacts.